Does Green Marketing Communication Affect Brand Image and Customer’s Purchase Desire? - Kurnia, Pepey Riawati; Narda, Livia; Sitio, Rike Penta (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The study aims to clarify the relationship between the active level of green marketing communication towards brand image and customer’s purchase desire, and examine brand image as a mediator between the green marketing communication, partially towards purchase desire. Green marketing communication consists of green action communication, green food communication, and green donation communication. This study is conclusive research and deployed the questionnaire method. The research population is the end customers who have done transactions at the green-concept food and beverages industry, live in Jabodetabek, and earn above the provincial minimum wage. The study provides empirical insight that active level of green marketing communication partially and significantly give a positive impact to brand image and customer's purchase desire. The study also proves that brand image significantly acts as a mediator between green marketing communication and purchase desire. As the research limitation due to the chosen population, the result may lack generalisability. Hence, researchers are encouraged to test the different propositions further. The study includes implications for practitioners in the food and beverage industry to improve their brand image and customer’s purchase desire by conducting green marketing communication actively. Currently, most practitioners are more focused on doing green marketing activities to affect business. This paper fulfills the need to study how the communication of green marketing affects brand image and customer’s purchase desire in food and beverages industry. Keywords: green marketing communication, green action communication, green food communication, green donation communication, brand image, purchase desire